PERBEDAAN KEMAMPUAN BERHITUNG PERMULAAN ANAK USIA 5-6 TAHUN MELALUI PERMAINAN TRADISIONAL LUMBUNG I TK PERTIWI PAYA TUSAM KECAMATAN WAMPU - Shintya Syaputri; Isa Hidayati (CV. ADIBA AISHA AMIRA, 2025)
This research is motivated by the presence of children whose numeracy skills have not developed well and the use of media that is less supportive during the learning process. The study aims to determine the differences in children's early numeracy skills using traditional lumbung games at Pertiwi Paya Tusam Kindergarten. This research is a quantitative approach with an experimental method with a one-group pretest-posttest design. The sample in this study was class B at Pertiwi Kindergarten, totaling 20 students with 13 boys and 7 girls using a purposive sampling technique. The data collection technique used was observation using an instrument. The data analysis technique used was descriptive statistics and inferential statistics. The data obtained were analyzed using the Wilcoxon signed rank test to see the differences in the treatments given. The results of this study show a significance value of 0.000 <0.05, which means that the use of traditional barn games has a significant difference in the early numeracy skills of children aged 5-6 years.